Monitoring of Nine Trace Elements in Chinese Herbal Medicine Tinospora sinensis (Lour.) Merr by ICP-MS - Xu, Fang; Yu-KuI, Rui; Wei, Tianxing (Asian Journal of Chemistry, 2010)
ICP-MS is the most efficient method to determine simultaneously the content of trace elements, heavy metals and rare earths in Chinese herbal medicines. The results proved that the Chinese herbal medicine Tinospora sinensis (Lour.) Merr contains great amount of trace elements, in which human-body-needed trace elements but rare earths elements and the heavy metals are very little. A method using ICP-MS with microwave digestion was studied for the determination of 29 elements including wholesome microelements, heavy metals and rare earth elements. There are five kinds of elements whose concentrations are more than 15 μg/g, they are Ca, Zn, Fe, Mn and B, especially the concentration of Ca is above 18192.35 μg/g, concentration of Mn is more than 1301.42 μg/g, Fe is more than 65.57 μg/g, whose high complexing ability can enhance treatment effects of Chinese herbal medicines. Most heavy metals and rare earth elements are lower than 0.1 μg/g, only the concentrations of Pb, Cr, La and Ce are more than 1 μg/g, so heavy metals and rare earth elements could have no effects on the treatment effects.